2011
DOI: 10.1097/yco.0b013e32833f5585
|View full text |Cite
|
Sign up to set email alerts
|

Current research on cognitive aspects of anxiety disorders

Abstract: Advances have clearly been made in the elucidation of the cognitive functioning associated with anxiety disorders. It remains unclear if particular cognitive profiles can help to distinguish anxiety disorders from one another, although emerging evidence suggests this may be the case. Further clarification will add to our understanding of the development and maintenance of these disorders, and may provide targets for future therapy and endophenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 69 publications
3
61
0
7
Order By: Relevance
“…More generally, attention and executive impairments characterize numerous psychiatric disorders. For example, attentional impairments are found in nearly every anxiety disorder (Ferreri, Lapp, & Peretti, 2011), eating disorders (Duchesne et al, 2004), bipolar disorder (Quraishi & Frangou, 2002), major depressive disorder (Zakzanis, Leach, & Kaplan, 1998), post-traumatic stress disorder (Horner & Hamner, 2002), schizophrenia (Pukrop & Klosterkotter, 2010), antisocial personality disorder (Dolan & Park, 2002), and borderline personality disorder (Ruocco, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, attention and executive impairments characterize numerous psychiatric disorders. For example, attentional impairments are found in nearly every anxiety disorder (Ferreri, Lapp, & Peretti, 2011), eating disorders (Duchesne et al, 2004), bipolar disorder (Quraishi & Frangou, 2002), major depressive disorder (Zakzanis, Leach, & Kaplan, 1998), post-traumatic stress disorder (Horner & Hamner, 2002), schizophrenia (Pukrop & Klosterkotter, 2010), antisocial personality disorder (Dolan & Park, 2002), and borderline personality disorder (Ruocco, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Pennington and Ozonoff point to a discriminant validity problem common to many neuropsychological tests, whereby symptomatically different behavioral disorders present with similar neuropsychological deficits [100]. For example, executive function impairments were found in nearly every anxiety disorder [153], as well as in eating disorders [154], bipolar disorder [155], major depressive disorder [156], post-traumatic stress disorder [89], schizophrenia [157], antisocial personality disorder [158] and borderline personality disorder [159].…”
Section: Review Abramovitch Mittelman Henin and Gellermentioning
confidence: 99%
“…Cognitive function is often impaired during emotional episodes with the most commonly reported defi cits in the domain of executive function (Ferreri, Lapp, & Peretti, 2011;Marazziti et al, 2010). Research has consistently demonstrated associations between acute stress or trauma exposure and poorer executive function (EF) DePrince et al, 2009;Horwitz and McCaffrey, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Research has consistently demonstrated associations between acute stress or trauma exposure and poorer executive function (EF) DePrince et al, 2009;Horwitz and McCaffrey, 2008). Previous studies reported impairments in executive activities of daily life associated with depressive mood (Patrick et al, 2004), anxiety (Ferreri, Lapp, & Peretti, 2011) and general distress (Gyurak, Goodkind, Kramer, Miller, & Levenson, 2012).…”
Section: Discussionmentioning
confidence: 99%